The use of distance learning in academic sections of the Minor Academy of Sciences of Ukraine (Pedagogy of Higher and Secondary Education, 2014)
Syoma S. А. The use of distance learning in academic sections of the Minor Academy of Sciences of Ukraine.The article is devoted to the problem of the use of distance learning in the educational process of scientific sections of the Minor Academy of Sciences of Ukraine. The author describes an experience of the combined distance learning in the scientific sections of chemical and biological department in the Sumy branch of Minor Academy of Science of Ukraine.
Keywords: Minor Academy of Sciences of Ukraine; out-of-school education; distance learning